The Role of Hofstede's Cultural Dimension Moderation on the Influence of Country of Origin on Buying Interest in the Electronics Industry - Phillip, Phillip; Halim, Rizal Edy (Syntax Corporation, 2025)
Country-of-origin (COO) is an important factor influencing purchase decisions, but its effectiveness remains debated due to inconclusive research. One key element affecting COO’s impact is consumer culture, yet studies on this topic are still limited. This research examines how Hofstede’s cultural dimensions influence the effectiveness of COO in shaping purchase intention. Hofstede's theory is the most widely used cultural framework and is highly regarded for explaining such phenomena. Unlike previous studies that primarily focused on the direct influence of Hofstede's cultural values on purchase intention in a limited manner, this study provides a comprehensive analysis of Hofstede's cultural values as moderating variables in the relationship between Country of Origin (COO) and purchase intention, covering all six cultural dimensions: power distance, masculinity, collectivism, uncertainty avoidance, indulgence, and long-term orientation. The study used data from 202 respondents (ages 25–34) in Jakarta and analysed it using moderated linear regression. The results indicate that the cultural dimensions of long-term orientation, uncertainty avoidance, and masculinity moderate the effect of Country of Origin (COO) on purchase intention for electronic products from Korea and China. In contrast, for local products, only long-term orientation and uncertainty avoidance were found to have a significant moderating effect. These findings are expected to contribute to the body of knowledge for readers and serve as a consideration in selecting appropriate methods and target markets for marketing strategies.